Condition of neuro-hormonal systems in traumatic brain injury and influence of Carbacetam - S. V. Ziablitsev; O. O. Starodubska (Zaporozhye State Medical University, 2017)
Use of GABA-ergic modulators in the traumatic brain injury (TBI) is actively investigated; their positive influence on brain circulation, inhibition of glutamate excitotoxicity, decrease of free radical damage, improvement of metabolism and power supply of neurons is determined. However, influence on functioning of neuro-hormonal systems in TBI isn't studied. The goal of given study was to investigate the Carbacetam effects on the condition of neuro-hormonal system in dynamics of experimental TBI. Methods. Research was carried out on white rat-males, age of six months, weighing 180-220 g. TBI was modeled by V. N. Elskyy and S. V. Ziablitsev model (2008) with the observance of Declaration of Helsinki adopted by the World Medical Association General Assembly, and general norms and principles of European Convention for the Protection of Vertebrate Animals. In comparison group 1 ml of normal saline solution was injected intraperitoneally. In animals of experimental groups 1 and 2 Carbacetam and Actovegin were injected intraperitoneally in doses of 5 mg/kg and 16 mg/kg of body weight, respectively, within 10 days after trauma. In blood the content of adrenocorticotropic hormone (ACTH), somatotropic hormone (STH), corticosterone and vasopressin were determined. Results and discussion. Administration of Carbacetam within 10 days after TBI prevented primary hyperactivation and contributed to the preservation of functioning of hypothalamic-neurohypophysis system and hypothalamic-pituitary-adrenal axis. In comparison with Actovegin, renewal of secretion of ACTH, corticosterone and vasopressin against the background of Carbacetam administration happened faster (from the 3rd to the 7th days). Administration of Carbacetam promoted prevention of the hyposecretion of STH significantly more than Actovegin. Identified modulating effects of Carbacetam could create conditions for more effective metabolism renewal and reparation processes in TBI. Conclusions. Administration of Carbacetam in the posttraumatic period renews functioning of neuro-hormonal systems more effectively than Actovegin, by prevention of their hyperactivation and exhaustion or excessive inhibition. Such an effect can be considered modulating with a positive restoring effect.